Penerapan Metode Taguchi untuk Optimasi Setting Parameter CNC Milling Terhadap Kekasaran Permukaan Material - Farizi Rachman Farizi Rachman; Bayu Wiro K; Tri Andi Setiawan; Pradita Nurkholies (Jurnal Teknologi dan Rekayasa Manufaktur, 2020)
The manufacturing industry in Indonesia is increasing along with the level of diverse human needs and triggering the development of technology, one of which is the machining process industry. Good product quality can be seen from the level of surface roughness, because surface roughness can affect performance related to the functional aspects of the product. In this study, analyzed the optimization of CNC milling parameters setting to surface roughness with 8 mm HSS end mill. S50C materials are widely used in manufacturing machinery such as mechanical base plate, gears, standart puch heads and other machine components. This research uses the Taguchi method. The Parameter used are spindle speed, feed rate and depth of cut with coolant as a constant variabel. The optimum parameters for surface roughness is obtained as spindle speed of 1100 rpm, feed rate of 46 mm/min and 0.5 depth of cut. With a significance level of 0.1 indicating that spindle speed has a significance effect with a contribution of 38.41% followed by feed rate of 34.16%